The case of the ugly suitor & other histories of love, gender, & nation in Buenos Aires, 1776-1870 - Shumway, Jeffrey M., 1968- (Engendering Latin America., 2005)
"In 1840 Gumerscindo Arroyo hoped to marry Francisca Canicoba, but her father forbade it. Consequently, Francisca took her father to court for permission to marry, where he objected on the grounds that Arroyo was simply too ugly."